Identification in the Economic Statistics - Valkauskas, Romualdas (Ekonomika, 1998)
The economic statistics is the economical statistical calculation. The economic statistics have special methods. They are: the statistical identical, the statistical classification, the statistical balance and the other economical calculation, the factorial index analysis, the calculation by econometrics methods. The economic statistics use methods other sciences, use methods of statistics. To the identical the processes of macroeconomics the economic statistics first of all use the method of statistical identical. The identical have not the universal features. The processes of macroeconomics must be identical separately. Readers in the article can to show procedures of identical the national wealth of Lithuania. Procedures have directions. The aim of economical statistical calculation the national wealth rise contents of directions.